Homeward orientation of displaced newts (Triturus cristatus, Lissotriton vulgaris) is restricted to the range of routine movements. Issue 3 (2nd July 2016) - Sinsch, U.; Kirst, C.
Abstract : Initial orientation of crested newts Triturus cristatus and smooth newts Lissotriton vulgaris was measured following passive displacement to arenas placed at 12 test sites 0.213–24.2 km distant from the breeding pond. Newts were transported by car without visual and olfactory outward journey information, but had full access to local orientation clues at the release site during the night and early morning before testing. Within the area of previous migratory experience, the initial directional choice of both species was significantly directed to home. Outside the area of familiarity, the initial orientation was indistinguishable from random in all but one site each at 3 and 20 km distance, respectively. We suggest that short-distance orientation was probably based on olfactory beaconing and on a learned spatial map integrating visual and olfactory information. The failure of homeward orientation following long-distance displacement indicates the absence of a spatial map which allows for extrapolation into unknown areas. The geomagnetic features of the study area include regional-scale irregularities probably impeding the derivation of reliable information from a geomagnetic map.